INTEGRITAS DAN SYARIAT ISLAM DALAM MEMBANGUN ETIKA PEMBELAJARAN AKUATIK BAGI MAHASISWA PGSD PENJAS - Mustika, Azmi Dian; Latifah, Syifa Asma; Parhan, Muhamad (Jendela Inovasi Daerah, 2025)
The integration of Islamic ethical values and the principle of integrity in physical education, especially in aquatic learning, is an important effort in forming student characters who are not only physically competent, but also moral and ethical. This research aims to describe students' perceptions of the integration of Islamic ethical values and the principles of integrity in aquatic learning in the PGSD Physical Education Study Program. The approach used was descriptive quantitative involving 41 students from the class of 2024 who were taking aquatics courses. Data collection was carried out through a questionnaire adapted from the Islamic Ethical Values Scale (IEVS) which consists of 20 items and covers four main dimensions, namely Islamic ethical values, application of sharia, integrity, and application of Islamic values in aquatic learning. The research results show that the majority of students have a positive perception of the integration of Islamic ethical values and the principle of integrity in the aquatic learning process. However, significant variations were found in several indicators indicating the need to develop a more inclusive and contextual curriculum in accordance with the values of Islamic law. It is hoped that these findings can become the basis for designing aquatic learning strategies that are not only technically competent, but also contain strong moral and spiritual values.